ESTETIKA LAYOUT: SOLUSI MENGGAET PENGALAMAN BELANJA YANG ATRAKTIF DAN CROSS SELLING PADA INDUSTRI RITEL - Rayzananda, Dheanggita; Febrianti, Dian Riska; Nanggala, Evan Reza; Azizah, Nur (Asosiasi Peneliti Manajemen Adat Indonesia, 2024)
The retail industry is a business engaged in the sale of goods and services with the scope of meeting people's daily needs. Layout arrangement in the retail industry is an important element because it can affect consumer preferences and income levels. Through the implementation of aesthetic layout strategies, a retail industry can provide attractive and effective visualization, to create an attractive shopping experience and increase sales through cross selling strategies. This research uses qualitative methods with literature study. The results of this research are that there is a connection between layout arrangement and shopping experience and increased income. Keywords: Attractive Shopping Experience; Cross Selling; Layout Aesthetics; Retail Industry.